Eritrograma glutationa reduzida e superóxido dismutase eritrocitários e metahemoglobina em equinos da raça Árabe submetidos a exercício em esteira: efeito da suplementação com vitamina E (dl-alfa-tocoferol) - Machado, Luciana Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
The objective of this study was to evaluate the oxidative erythrocyte metabolism in equines submitted to exercise on high-speed treadmill and the effect of vitamin E supplementation. Eight adults Arabian horses, males and females, were divided: control group (CG) and group supplemented with vitamin E (EG), (1000 UI/animal/day). All the equines were submitted to exercise with two incremental tests (T1 and T2). Exercise protocol for two tests started with 1.8m/s for 5 min, 4m/s for 3 min, 6m/s for 2 min and right after, periods of 1 min, challenging the equines with increasing speeds until the animals had no condition to keep the exercise on a treadmill inclined at 7%. Between the tests, a training protocol was performed for 20 days. Blood samples were taken before, during, and until 120 hours after exercise to determine erytrogram, erythrocyte reduced glutathione (GSH), superoxide dismutase (SOD), methemoglobin, erythrocyte osmotic fragility (EOF), total plasmatic protein (TPP), seric malondialdehyde (MDA) and vitamin E, seric enzymatic activity of aspartate aminotransferase (AST) and creatine kinase (CK), blood lactate and bloodgas. The results were compared by non-parametric Mann-Whitney and Friedman tests. Although differences were detected in only a few variables, it was possible to see increase in erytrogram and TPP by spleenic contraction and/or decrease of the plasma volume, and increase the erythrocyte volume by swelling. Sport anemia was observed between 24h and 120h after the exercise. The methemoglobin was compatible with the physiological levels and the EOF increased during the exercise in both groups. The MDA elevation confirm the liperoxidation by exercise effect, less intense EG by the supplementation with vitamin E. The exercise also induced increase of AST and CK enzymes, increase of blood lactate and metabolic acidosis.
Keywords: Patologia clinica veterinaria - Equinos; Equino; Vitamina E na nutrição; Fisiologia do exercício; Malondialdeído; Metabolismo oxidativo eritrocitário; Equine; Physiology of exercise; Malondialdehyde; Erythrocyte oxidative metabolism; Vitamin E